Hospitalist Perspective of Interactions with Medicine Subspecialty Consult Services. Issue 5 (22nd November 2017) - Adams, Traci N.; Bonsall, Joanna; Hunt, Daniel; Puig, Alberto; Richards, Jeremy B.; Yu, Liyang; McSparron, Jakob I.; Shah, Nainesh; Weissler, Jonathan; Miloslavsky, Eli M.
Abstract : BACKGROUND: Medicine subspecialty consultation is becoming increasingly important in inpatient medicine. OBJECTIVE: We conducted a survey study in which we examined hospitalist practices and attitudes regarding medicine subspecialty consultation. DESIGN AND SETTING: The survey instrument was developed by the authors based on prior literature and administered online anonymously to hospitalists at 4 academic medical centers in the United States. MEASUREMENTS: The survey evaluated 4 domains: (1) current consultation practices, (2) preferences regarding consultation, (3) barriers to and facilitating factors of effective consultation, and (4) a comparison between hospitalist–fellow and hospitalist–subspecialty attending interactions. RESULTS: One hundred twenty‐two of 261 hospitalists (46.7%) responded. The majority of hospitalists interacted with fellows during consultation. Of those, 90.9% reported that in‐person communication occurred during less than half of consultations, and 64.4% perceived pushback at least "sometimes" in their consult interactions. Participants viewed consultation as an important learning experience, preferred direct communication with the consulting service, and were interested in more teaching during consultation. The survey identified a number of barriers to and facilitating factors of an effective hospitalist–consultant interaction, which impacted both hospitalist learning and patient care. Hospitalists reported more positive experiences when interacting with subspecialty attendings compared to fellows with regard to multiple aspects of the consultation. CONCLUSION: The hospitalist–consultant interaction is viewed as important for both hospitalist learning and patient care. Multiple barriers and facilitating factors impact the interaction, many of which are amenable to intervention.